PENGEMBANGAN PERANGKAT PEMBELAJARAN BERORIENTASI MODEL PEMBELAJARAN BERDASARKAN MASALAH PAPA POKOK BAHASAN SUMBER DAYA ALAM DI KELAS 4 SD LABORATORIUM - Dian Kusmaharti (WAHANA, 2011)
In this research was developed the problem-based instruction model-oriented Natural Science instruction instrument. Therefore, this research used the developmental research design. The instruction instrument developed was involving the Instruction Implementation Plan (RPP), Student teaching material, Student Activity Sheet (LKS), and Learning Outcome Test (THB). Instruction instrument development referred to the stages of Four D model-based instruction instrument development. The instruction instrument was tried out to the 41 grade students of the UNESA Laboratory Elementary School of Ketintang with subjects as many as 15 students (class IVB) in try-out 1 and 28 students in try-out 2. This research had the purpose to know the quality of instruction instrument development results and to know the try-out results of problem-based instruction-oriented instruction instrument. Try-out design used was One Group Pretest-Posttest Design. Based on the data analysis results of the try-out 1 and try-out 2 research results known that the developed instruction instrument has had the good quality and reasonable to use. This case was based on the instruction instrument validity was good and have been reasonable to use as the instruction instrument because of it has already met with validity standard established by the Educational National Standard Agency/BSNP. Beside that, also based on the student teaching material difficulty level and the students teaching material readability with the easy to comprehend criteria. The sensitivity of positive valued item and the instrument average reliability were above 75%. The effective instruction instrument try-out supported the teaching learning activity based on the instruction management average of good and very good categories. The whole syntaxes of problem-based instruction were 100% implemented. Student activities during the teaching learning activity showed that the students learned active. Students' responses to the problem-based instruction-oriented instruction instrument were positive. Likewise with the results of cognitive learning and the students learning process showing the individual and classical completeness as large as 100%. Of the instruction instrument development results, the results of try-out 1 and try-out 2 showed that the quality of problem based instruction instrument developed was good and have met the worthiness as the instruction instrument in the Natural Science subject matter of 4th grade of Elementary School on the natural resources topic. This problem based instruction instrument developed could be said as effective to support the teaching learning activity.